A comparative analysis of node replica detection schemes in wireless sensor networks. (February 2016) - Mishra, Alekha Kumar; Turuk, Ashok Kumar
Abstract: Wireless sensor networks are exposed to various kinds of security threat. The node replication attack is application-independent and can be launched by an adversary just by capturing a single sensor from the network. The post-capture impact of this attack is serious as an adversary can launch various insider attacks with the help of replicas that are deployed in the network. Counter-measures for node replication attack have drawn the attention of many researchers in this field. The first step towards handling a node replication attack is to detect the existence of replicas and remove them from the network. A number of replica detection schemes have been proposed in the literature. However, only a few survey articles exist based on replica detection schemes. Most of these survey lacks comparative analysis on the existing schemes, and are limited only to a few referred schemes. In this paper, we have classified the existing replica detection schemes considering a higher number of parameters than the existing schemes, and highlighted advantages and disadvantages of the contributions. A detailed comparative analysis of the existing schemes are made based on their communication cost, message overhead, storage requirement, and number of replica detectors per node. We have simulated a few mostly referred detection schemes using Castalia and analysed their performance in terms of detection probability, average number of packets sent/received, detection time, and energy consumption. Abstract : Highlights: Classification and analysis of various replica detection schemes in Wireless Sensor Networks. Most of the full distributed detection schemes are location-dependent. Number of replica detector per node is higher in location-dependent schemes. Size of the claim message is smaller in the scheme proposed by Znaidi et al. Simulation results depict that RED detection scheme has higher detection probability and SET detection scheme has lower communication overhead.